Biochemistry : - Appling, Dean R. (Pearson, 2016)
1. Biochemistry and the Language of Chemistry 2. The Chemical Foundation of Life: Weak Interactions in an Aqueous Environment 3. The Energetics of Life 4. Nucleic Acids 5. Introduction to Proteins: The Primary Level of Protein Structure 6. The Three-Dimensional Structure of Proteins 7. Protein Function and Evolution 8. Enzymes: Biological Catalysts 9. Carbohydrates: Sugars, Saccharides, Glycans 10. Lipids, Membranes, and Cellular Transport 11. Chemical Logic of Metabolism 12. Carbohydrate Metabolism: Glycolysis, Gluconeogenesis, Glycogen Metabolism, and the Pentose Phosphate Pathway 13. The Citric Acid Cycle 14. Electron Transport, Oxidative Phosphorylation, and Oxygen Metabolism 15. Photosynthesis 16. Lipid Metabolism 17. Interorgan and Intracellular Coordination of Energy Metabolism in Vertebrates 18. Amino Acid and Nitrogen Metabolism 19. Nucleotide Metabolism 20. Mechanisms of Signal Transduction 21. Genes, Genomes, and Chromosomes 22. DNA Replication 23. DNA Repair, Recombination, and Rearrangement 24. Transcription and Post-transcriptional Processing 25. Information Decoding: Translation and Post-translational Protein Processing 26. Regulation of Gene Expression